Do romance ao filme: um olhar sobre crônica da casa assassinada - Almeida, Londina da Cunha Pereira de (2016)
The objective of this thesis is to analyze how the narrative instances of point of view and space compete to create the intimate aura of the novel Crônica da casa assassinada (1959), by Lúcio Cardoso. Using the theory of Jean Pouillon, in O tempo no romance (1974), on the point of view, we try to understand the subjective effects drawn from multiple perspectives looking, combined with the intimate writings of the ten characters-narrators of the text. The variety of versions upon the protagonist of the narration helps to make her indecipherable to our eyes, and leads us to suspect of what some narrators say driven by a jumble of feelings. We also found the space to which these characters-narrators are confined, for being isolated and tedious, contributes to the consolidation of their distress and interpersonal conflicts that settle among them. Moreover, this space is seen in a perspective away, so it expresses the personal impression that each of them has of Chácara dos Meneses. To support our analysis of space, we use essentially the study by Osman Lins, in Lima Barreto e o espaço romanesco (1976), Michel Foucault, in “Outros espaços” (2009) and Gaston Bachelard, in Poéticas do Espaço (2008), because they evaluate subjectively the relation character versus space. The last chapter provides a study of the same narrative instances in the adaptation of the novel to cinema, in the production by Paulo Cesar Saraceni, A casa assassinada (1971). In this chapter we use a more sociological approach to the adaptation process, not focusing exclusively on the aesthetic elements of the text. Whereas the adaptation is not only the product, as a process that sees the film as artistic representation as well as socio-cultural, our analyses are supported by the studies of Linda Hutcheon in Uma teoria da adaptação (2011). Despite the broad possibilities of modifications that adaptation offers, the filmmaker chose to keep the main aspects of the text, which led us to assess how sued the narrative focus and space in the filmic texture.